1970
DOI: 10.3329/bjb.v40i1.7992
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphorus deficiency on accumulation of biochemical compounds in lentil (<i>Lens culinaris</i> Medik.)

Abstract: Phosphorus deficiency caused a decrease in the accumulation of reducing sugar in the leaves and stems but increased in the roots of lentil (Lens culinaris Medik.). Accumulation of insoluble protein was depressed in lentil following P-deficiency. Phosphorus deficiency increased proline and phenolic compounds in roots and stems and anthocyanin in leaves compared to control. Key words: Phosphorus deficiency; Accumulation; Biochemical compounds DOI: http://dx.doi.org/10.3329/bjb.v40i1.7992 Bangladesh J. Bot. 40(1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 15 publications
5
16
0
Order By: Relevance
“…The plants with a lower supply of phosphorus in the soil developed less dynamically and produced less abundant leaves, despite having a better habit, particularly in the initial stages of development. This is confirmed in a study on lentil plants by Sarker and Karmoker [22], who found that phosphorus deficiency decreases accumulation of reducing sugars in the leaves and stems. Grzebisz [23] pointed out that good phosphorus supply to plants is manifested as increased content of structural constituents -mainly lignin -in the plant stems.…”
Section: Discussionsupporting
confidence: 71%
“…The plants with a lower supply of phosphorus in the soil developed less dynamically and produced less abundant leaves, despite having a better habit, particularly in the initial stages of development. This is confirmed in a study on lentil plants by Sarker and Karmoker [22], who found that phosphorus deficiency decreases accumulation of reducing sugars in the leaves and stems. Grzebisz [23] pointed out that good phosphorus supply to plants is manifested as increased content of structural constituents -mainly lignin -in the plant stems.…”
Section: Discussionsupporting
confidence: 71%
“…5b). Similarly, it decreased reducing sugar in the leaves and stem but stimulated that in the root (11) . Phosphorus deficiency caused a reduction in total sugar content in the root from 21-22% from 24 to 72 hrs of treatment (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…It increased carbohydrate concentration in the root of bean (9) and maize (10) . It decreased reducing sugar content in the leaves and stem but stimulated in the root (11) .…”
Section: Introductionmentioning
confidence: 99%
“…The increase was greater for the treatments with lower doses of P, showing that the expression of this enzyme is an early response in cape gooseberry seedlings to a deficiency of this element and may be related to the observed decrease in EL. Similarly, POD enzyme activity was low, but was higher in treatments with lower doses of P. It has also been reported that P deficiency can increase the Pro content in roots and stems in lentil plants (Sarker et al, 2011) and in leaves and roots in beans that are deficient in P (Juszczuk et al, 2001). The observed Pro increase in P0, P6 and P12, which was higher at 30 dt and 60 dt, could be another response of cape gooseberry seedlings to reduce ROS caused by an imbalance in photosynthesis (Hare et al, 1998).…”
Section: Antioxidant Enzymes Proline and Protein Contentmentioning
confidence: 80%
“…In tomato plants, which are tolerant to low P availability, increased peroxidase activity and anthocyanin accumulation have been observed (Khavari-Nejad et al, 2009). Also, an increase in the proline content of roots and stems (Sarker and Karmoker, 2011) has been found in lentil plants (Lens culinaris Medik). P. peruviana L. is grown from 1500 m to 3000 m a.s.l.…”
Section: Introductionmentioning
confidence: 92%